Asuhan Keperawatan Medikal Bedah Pada Pasien Penyakit Paru Obstruksi Kronik (Ppok) Di Ruangan Muzdhalifah Rumah Sakit Aisyiyah Pariaman - Nikmatul Hasana; Mike Asmaria; Hima Yessi; Debby Silvia Dewi (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
Chronic Obstructive Pulmonary Disease (COPD) is a chronic lung disease characterized by progressive airflow limitation and is one of the leading causes of death worldwide. The WHO reports that COPD ranks third as a global cause of death with approximately 3.5 million deaths per year. The prevalence of COPD in Indonesia reaches 5.6%, in West Sumatra 3.5%, and Aisyiyah Pariaman Hospital recorded 27 cases in 2025. This case study aims to describe the implementation of nursing care for a COPD patient in the Muzdhalifah Ward at Aisyiyah Pariaman Hospital. The method used is a case study approach comprising assessment, nursing diagnosis, intervention planning, implementation, evaluation, and nursing documentation. The case study was conducted on Mr. M from February 26 to March 2, 2026. Assessment results revealed dyspnea, productive cough, and sleep disturbance. Nursing diagnoses included ineffective airway clearance, ineffective breathing pattern, activity intolerance, disturbed sleep pattern, and knowledge deficit. Following 5 days of nursing care, all nursing diagnoses were resolved and the patient was discharged upon physician recommendation. Patients and families are expected to adopt a healthy lifestyle, perform routine check-ups, and adhere to treatment to prevent recurrence.